2013
DOI: 10.1039/c3nr33777d
|View full text |Cite
|
Sign up to set email alerts
|

Development of drug loaded nanoparticles for tumor targeting. Part 1: synthesis, characterization, and biological evaluation in 2D cell cultures

Abstract: Nanoparticles (NPs) are being extensively studied as carriers for drug delivery, but they often have limited penetration inside tumor. We envision that by targeting an endocytic receptor on cell surface, the uptake of NPs can be significantly enhanced through receptor mediated endocytosis. In addition, if the receptor is recycled to cell surface, the NP cargo can be transported out of the cells, which are then taken up by neighboring cells thus enhancing solid tumor penetration. To validate our hypothesis, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 72 publications
2
20
0
Order By: Relevance
“…Nanobeads were chosen here for proof of concept where similarly sized particles loaded or decorated with small molecular drugs, proteins, or siRNA can be encapsulated within these hydrogels for localized release for specific applications of interest. 69, 70 Note, a more continuous release profile upon bulk degradation by thiol exchange or hydrolysis would be expected for biologics (e.g., antibodies and other therapeutic proteins) directly encapsulated within these types of gels; protein release will be driven by diffusion as the mesh size of the hydrogel increases commensurate with degradation, as observed in our earlier work with dually degradable hydrogels. 37 Overall, these results support the hypothesis that the release of cargo can be tuned by controlling the degradation rate and, in principle, such a strategy could be employed for spatiotemporal control over release of cargo molecules in biological systems.…”
Section: Degradation Mediated Release Of Model Cargo Nanobeadsmentioning
confidence: 82%
“…Nanobeads were chosen here for proof of concept where similarly sized particles loaded or decorated with small molecular drugs, proteins, or siRNA can be encapsulated within these hydrogels for localized release for specific applications of interest. 69, 70 Note, a more continuous release profile upon bulk degradation by thiol exchange or hydrolysis would be expected for biologics (e.g., antibodies and other therapeutic proteins) directly encapsulated within these types of gels; protein release will be driven by diffusion as the mesh size of the hydrogel increases commensurate with degradation, as observed in our earlier work with dually degradable hydrogels. 37 Overall, these results support the hypothesis that the release of cargo can be tuned by controlling the degradation rate and, in principle, such a strategy could be employed for spatiotemporal control over release of cargo molecules in biological systems.…”
Section: Degradation Mediated Release Of Model Cargo Nanobeadsmentioning
confidence: 82%
“…HAp nanoparticles can slow down the growth of various cancer cells, particularly human glioma cells [16]. Organ-targeting or tumor-targeting via drug-loaded nanoparticles demonstrated their ability to act on specific receptors [17]. The targeting of receptors by HAp nanocrystals was proposed as the basis for the utilization of HAp doped with rare earth elements for noninvasive medical imaging at the molecular level [18].…”
Section: Introductionmentioning
confidence: 99%
“…40 We recently reported that conjugating the anticancer drug doxorubicin (DOX) on the surface of nanoparticles (Figure 1) rendered the DOX-resistant NCI-ADR-RES ovarian cancer cells more sensitive to drug treatment most likely through modulation of the intracellular distribution of drug. 27 The interaction between the hyaluronan (HA) coating on the nanoparticles and the CD44 receptor overexpressed on the external cell membranes of SKOV-3 epithelial ovarian cancer cells facilitated the enhanced uptake of the nanoparticles by cells in 2D cell cultures, 41 and mediated deeper penetration of the nanoparticles in 3D SKOV-3 cancer spheroids through receptor mediated transcytosis. 42 In this manuscript, we investigate the efficacy of DOX conjugated onto HA-SPIONs in vivo in subcutaneous (S.C.) and intraperitoneal (I.P.)…”
Section: Introductionmentioning
confidence: 99%